Penerapan Bimbingan Kelompok dengan Menggunakan Teknik Self-Management dalam Meningkatkan Pemahaman Tentang Etika Pergaulan pada Santri - Ali Ahmad Alif; M. Amin Sihabuddin; Zhila Jannati (Scidacplus, 2024)
Muslims really uphold ethics in various matters, one of which is ethics in relationships between people. The process of providing an understanding of social ethics must be understood well, especially for children who are studying in educational or religious institutions. This research aims to find out a picture of the understanding of students' social ethics before implementing group guidance with self-management techniques, to find out how group guidance with self-management techniques is applied in increasing understanding of students' social ethics, to find out the picture after group guidance with self-management techniques is given in increasing understanding. student social ethics. This research is qualitative research, the subjects of this research are 1st grade students of MTs Pondok Pesantren Al-Amalul Khair Palembang. The data collection techniques used were observation, interviews and documentation techniques. Next, the data is presented in the form of words, then the data is analyzed and conclusions are drawn, so that it is easy to understand for both researchers and people who read. The research results obtained are: First, the picture before group guidance was carried out using self-management techniques: The understanding is only limited to the children's knowledge, so it cannot be said to understand well. Second, the implementation of group guidance using self-management techniques: carried out in 4 stages, namely the preparation stage, formation stage, transition stage, and activity stage and carried out in 4 meetings with different material for each meeting. Third, the picture after group guidance using self-management techniques: children can understand the material provided through group guidance, but cannot explain the material given by the researcher again.